Mobile city : emerging media, space, and sociality in contemporary Berlin - Kraemer, Jordan H., 1978- (Cornell University Press, 2024)
"In late-aughts Berlin, emerging media, from Facebook to smartphones, reworked place-based identities, facilitating urban, middle-class aspirations to cosmopolitan connection while transforming experiences of everyday life. These scalar transformations were lived out through ordinary practices that reconfigured sociality, mobility, and urban space"-- Provided by publisher.
Keywords: Social media and society -- Germany -- Berlin -- History -- 21st century.; Online social networks -- Germany -- Berlin -- History -- 21st century.; Digital media -- Social aspects -- Germany -- Berlin.; City and town life -- Germany -- Berlin -- History -- 21st century.; Social change -- Germany -- Berlin -- History -- 21st century.; Place attachment -- Social aspects -- Germany -- Berlin.; Spatial behavior -- Social aspects -- Germany -- Berlin.; Group identity -- Germany -- Berlin -- History -- 21st century.; Berlin (Germany) -- Social conditions -- 21st century.; Berlin (Germany) -- Social life and customs -- 21st century.; Vie urbaine -- Allemagne -- Berlin -- Histoire -- 21e siècle.; SOCIAL SCIENCE / Media Studies